Evaluation of maximal lactate steady state in middle-aged hypertensive women - Ferreira, Maycon Júnior; Jarrete, Aline Pincerato; Esposti, Rodrigo Degli; Sponton, Carlos Henrique Grossi; Anaruma, Chadi Pelegrini; Zanesco, Angelina (Universidade Estadual Paulista, 2018)
AbstractAIM The aim of this study was to investigate the lactate response in physically inactive hypertensive women submitted to the treadmill maximal lactate steady state (MLSS) protocol.METHODS Twenty-two hypertensive women (40 - 64 years) performed a familiarization period of walking on the treadmill following by one incremental test for estimating the initial workload for exercise testing. MLSS protocol was composed by walking in a treadmill during thirty minutes with fixed velocity in 5.5 km/h. Incline was used for determination of the intensity of each volunteer. Blood samples were collected from the ear lobe in the rest period, minute 10th and at the end of the test (minute 30th or at exhaustion time point) for lactate analysis.RESULTS Hypertensive women showed a lower lactate concentration at MLSS (3.25 ± 0.81 mmol/L) as compared with data obtained in the literature (4 mmol/L), approximately 18.8%. Neither inclines nor age affected MLSS parameters in the population. A positive and strong correlation was found between incline and MLSS, as well as incline and lactate level at minute 30th, even when adjusted by age factor.CONCLUSION Physically inactive hypertensive women show a lower MLSS than the average established in the literature but within the range of variations previously reported. Furthermore, a higher MLSS incline correlates positive and directly with higher lactate concentrations for the same aerobic capacity regardless of age.
Keywords: aerobic performance; maximal lactate steady state; hypertensive women